2014
DOI: 10.1158/1078-0432.ccr-13-1687
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of FOXO3a Promotes Tumor Metastasis and Is Associated with Metastasis-Free Survival of Patients with Clear Cell Renal Cell Carcinoma

Abstract: Purpose: To explore the mechanisms underlying clear-cell renal cell carcinoma (ccRCC) metastasis using transcriptional profiling and bioinformatics analysis of ccRCC samples, and to elucidate the role of FOXO3a in ccRCC metastasis.Experimental Design: Gene expression profiling was performed using four primary metastatic and five primary nonmetastatic ccRCC samples. The mRNA and protein levels of FOXO3a in ccRCC samples were investigated by real-time reverse transcription PCR and immunohistochemistry, respectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 45 publications
3
104
1
Order By: Relevance
“…For OS-RC-2, inhibitory effect of KLF6 on microvessel forming could be reversed by E2F1 (P < 0.001). Ã , P < 0.05; ÃÃ , P < 0.01; ÃÃÃ , P < 0.001. the orthotopic and metastatic model, due to its pulmonary metastatic property (22). ShE2F1 group mice exhibited a strong reversed effect (Fig.…”
Section: Klf6 Downregulation Promotes E2f1-mediated Cell Proliferatiomentioning
confidence: 95%
“…For OS-RC-2, inhibitory effect of KLF6 on microvessel forming could be reversed by E2F1 (P < 0.001). Ã , P < 0.05; ÃÃ , P < 0.01; ÃÃÃ , P < 0.001. the orthotopic and metastatic model, due to its pulmonary metastatic property (22). ShE2F1 group mice exhibited a strong reversed effect (Fig.…”
Section: Klf6 Downregulation Promotes E2f1-mediated Cell Proliferatiomentioning
confidence: 95%
“…FoxO3 acts as a transcription factor and triggers apoptosis through induction of death genes such as FasL and Bim1 [34]. Ni et al showed that FOXO3a silencing promoted invasiveness of renal cancer cells and metastasis of renal cancer cells in vivo [35]. Furthermore, Gopinath et al demonstrated a functional requirement for FOXO3a as a regulator of the Notch signaling pathway, a pathway critical for the self-renewal and maintenance of CSCs [36].…”
Section: Discussionmentioning
confidence: 99%
“…Ginestier et al showed that simvastatin targeted CSCs through RhoA/CDKN1B signaling [6]. Similarly, Ni et al observed downregulation of FOXO3a increased metastasis and predicted worse metastasis-free survival in patients with renal cell carcinoma [35]. This paper distinguishes itself from Ginestier et al because they looked at tumor initiation and this study focused on metastasis initiation.…”
Section: Discussionmentioning
confidence: 99%
“…Further, they showed that statin therapy regulates protein FOXO3a activation, suggesting a potential mechanism for simvastatin's anti-metastatic effects (Wolfe et al 2015). Downregulation of FOXO3a increases metastasis formation and predicts worse metastasis-free survival in patients with renal cell carcinoma (Ni et al 2014). These results suggest that statins can inhibit metastasis development and progression based on their ability to affect signal molecules involved in regulation of cell migration and cell proliferation.…”
Section: Impact On Angiogenesis and Metastasismentioning
confidence: 99%